The effects of Malaysian herb, Labisia pumila var. alata on oestrous cyclicity and reproductive parameters of nulliparous rats - Wan Ezumi Mohd Fuad,; Hasnan Jaafar,; Siti Amrah Sulaiman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Numerous nutraceutical products containing the powdered or extracted parts of Labisia pumila (Myrsinaceae) have been widely available for years in Malaysia, aimed at women of reproductive age. However, there is scarce of information concerning the effects of this plant on the reproductive function of nulliparous females prior to the present study. The toxicity potential of Labisia pumila var. alata (LPA) on oestrous cycle and reproductive parameters was evaluated in groups of 40 virgin rats. They were administered with LPA at the doses of 0 (control), 20, 200 or 1000 mg/kg/day for duration of three weeks. The results obtained indicated that the administration of LPA at all dose levels did not cause mortality nor show noticeably any treatment-related signs of toxicity on the physical appearance, behaviour and body weight of all the rats studied. The pattern and length of oestrous cyclicity as well as the changes in reproductive hormones were statistically comparable among groups. No indications of abnormalities in the histology of uterus and vagina were observed. However, the presence of ovarian follicular cysts has raised apprehension that requires further investigation. The current findings suggested that oral treatment of LPA were associated with toxicity concerns.